Relativity: An Alternative Interpretation In the Light of The Existence of An Extra Spatial Dimension – A Systematic Review - Cataldo, Carmine (JOURNAL OF ADVANCES IN PHYSICS, 2020)
This paper represents the latest revision of a portion of the research work, still in progress, carried out by the author during the last four years. The overall aim of the study fundamentally consists in showing how, while postulating the absoluteness of time, the validity of the relativistic equations may be formally preserved. Starting from the writing of the first Friedmann – Lemaître Equation (and therefore from General Relativity), a Simple-Harmonically Oscillating Universe (flat, upper-bounded, conventionally singular at